The position of Iraqi popular organizations and associations on the Vietnamese issue 1958-1968 (Journal of the College of Basic Education, 2022)
This study attempts to uncover the role of Iraqi popular organizations and associations in supporting the Vietnamese cause and their positions on the successive events in Vietnam and the struggle of the Vietnamese people against the colonial powers during the years 1958-1968.